Assessing internet risks among high school students in Kanagawa Prefecture: A 2019 survey and the analysis of factors involving underage internet use - Mitsuteru Tashiro (International Telecommunications Society (ITS), 2024)
In order to mitigate the risk of luring minors using the internet, this study analyzed the current status of risk and its underlying factors based on responses in a questionnaire distributed among high school students in Kanagawa Prefecture, Japan. Results showed that the experience of receiving a message from a stranger saying "I want to meet you" is higher for female students who publish photographs of their face on social media or do not follow family rules on the use of the internet. The proportion of female students responding to a request of sending their photographs with "no" or "consult with a parent or teacher" was higher if they had experience in information literacy education within a year, had content filtering installed on their smartphones, or followed family rules.
Keywords: 330; luring minors; smartphones; Social Networking Service; Selfie